Oral administration of synthetic selenium nanoparticles induced robust Th1 cytokine pattern after HBs antigen vaccination in mouse model. Issue 1 (January 2017) - Mahdavi, Mehdi; Mavandadnejad, Faranak; Yazdi, Mohammad H.; Faghfuri, Elnaz; Hashemi, Hura; Homayouni-Oreh, Somayeh; Farhoudi, Ramin; Shahverdi, Ahmad R.
Summary: Hepatitis B virus (HBV) infection is known as a life-threatening liver infection and leads to chronic liver disease if left untreated. Nevertheless, the prevalence of HBV infection has been reduced by an approved vaccination approach using recombinant Hepatitis B surface Antigen (HBsAg) and Alum, known as the HBV vaccine. Alum can be used as an adjuvant to increase HBsAg immunogenicity as a strong Th2 stimulator. There is a vital need to stimulate Th1 immunity by HBsAg vaccination; however, the present vaccine does not induce a prophylactic immune response in some groups. The main aim of the present study was to induce a Th1 cytokine pattern and stimulate an immune response after HBsAg vaccination. Experimental mice were fed selenium nanoparticles (SeNPs) and were later immunized with 5 μg of Hepatitis B Vaccine. After a period of 30 days, the experimental animals were given two booster doses of SeNPs during their vaccination course. Group one, i.e., the control vaccine group, was only administered the HBsAg vaccine. The two treated groups, Groups 2 and 3, were daily fed different doses of SeNPs (100 μg and 200 μg, respectively) via gavage. Group four was considered the control group and was only given phosphate buffered saline (PBS). Lymphocyte proliferation, IFN-γ and IL-4 levels, total antibody and the isotypes of IgG1, IgG2a, IgG2b, and IgM were measured by Enzyme Linked Immunosorbent Assay (ELISA). The administration of SeNPs and the HBs antigen vaccine affected the lymphocyte proliferation; moreover, the total antibody responses also increased the IFN-γ level and induced a Th1 response. Conclusions: The present study proposed that the administration of SeNPs with a conventional HBs antigen vaccine induces a better immune response with a Th1 bias.